Critical information infrastructures security : 12th International Conference, CRITIS 2017, Lucca, Italy, October 8-13, 2017, Revised selected papers /: 12th International Conference, CRITIS 2017, Lucca, Italy, October 8-13, 2017, Revised selected papers. (2018) - Unknown
No abstract available